Discovery of 1, 2, 3, 4-tetrahydropyrimido[1, 2-a]benzimidazoles as novel class of corticotropin releasing factor 1 receptor antagonists. Issue 9 (15th May 2018) - Kojima, Takuto; Mochizuki, Michiyo; Takai, Takafumi; Hoashi, Yasutaka; Morimoto, Sachie; Seto, Masaki; Nakamura, Minoru; Kobayashi, Katsumi; Sako, Yuu; Tanaka, Maiko; Kanzaki, Naoyuki; Kosugi, Yohei; et al.
Graphical abstract: Abstract: A new class of corticotropin releasing factor 1 (CRF1 ) receptor antagonists characterized by a tricyclic core ring was designed and synthesized. Novel tricyclic derivatives2a –e were designed as CRF1 receptor antagonists based on conformation analysis of our original 2-anilinobenzimidazole CRF1 receptor antagonist. The synthesized tricyclic derivatives2a –e showed CRF1 receptor binding activity with IC50 values of less than 400 nM, and the 1, 2, 3, 4-tetrahydropyrimido-[1, 2- a ]benzimidazole derivative2e was selected as a lead compound with potent in vitro CRF1 receptor binding activity (IC50  = 7.1 nM). To optimize the pharmacokinetic profiles of lead compound2e, we explored suitable substituents on the 1-position and 6-position, leading to the identification of compound42c -R, which exhibited potent CRF1 receptor binding activity (IC50  = 58 nM) with good oral bioavailability (F = 68% in rats). Compound42c -R exhibited dose-dependent inhibition of [ 125 I]-CRF binding in the frontal cortex (5 and 10 mg/kg, p.o.) as well as suppression of locomotor activation induced by intracerebroventricular administration of CRF in rats (10 mg/kg, p.o.). These results suggest that compound42c -R successfully binds CRF1 receptors in the brain and exhibits the potential to be further examined for clinical studies.